2018
DOI: 10.1002/cbin.10919
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of osteogenesis of human amniotic mesenchymal stem cells by sodium butyrate

Abstract: Human amniotic membrane-derived mesenchymal stem cells (hAMSCs) draw great interests for regenerative medicine due to convenient availability and low immunogenicity. However, suboptimal culture conditions limit their application. In recent years, small molecules have proven powerful in regulating stem cell fates and can be applied to stimulate their function. In the present study, the impacts of sodium butyrate (NaBu), a histone deacetylase inhibitor (HDACi), on hAMSCs were investigated. It was shown that NaBu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Similarly, various pharmacologically active chemicals promote osteogenesis through activation of TAZ. These include TM-25659 (Jang et al, 2012), sodium butyrate (Fan et al, 2018), lipopolysaccharide (Xing et al, 2019), 1α,25-dihydroxyvitamin D3 (Ji et al, 2019), icariin (Wei et al, 2017;Ye et al, 2017), epicatechin gallate (ECG) (Byun et al, 2014b), phorbaketal A (Byun et al, 2012a), kaempferol (Byun et al, 2012b), and poncirin (Yoon et al, 2011).…”
Section: Role Of Yap/taz In Stem Cell Self-renewal and Maintenance Ofmentioning
confidence: 99%
“…Similarly, various pharmacologically active chemicals promote osteogenesis through activation of TAZ. These include TM-25659 (Jang et al, 2012), sodium butyrate (Fan et al, 2018), lipopolysaccharide (Xing et al, 2019), 1α,25-dihydroxyvitamin D3 (Ji et al, 2019), icariin (Wei et al, 2017;Ye et al, 2017), epicatechin gallate (ECG) (Byun et al, 2014b), phorbaketal A (Byun et al, 2012a), kaempferol (Byun et al, 2012b), and poncirin (Yoon et al, 2011).…”
Section: Role Of Yap/taz In Stem Cell Self-renewal and Maintenance Ofmentioning
confidence: 99%
“…Inhibition of the activity of HDACs with specific or pan HDAC inhibitors, enhances osteogenic differentiation in detriment of adipogenic differentiation in many cellular models [6,30,40]. These effects could be a consequence of the change of the acetylation state in the N-term of histone H3 and/or H4.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that NaBu regulates osteogenesis in human amniotic mesenchymal stem cells and other stem cells [30]. We treated ASC with NaBu at a final concentration of 0.5 mM for three days before the induction of the osteogenic differentiation.…”
Section: Subcellular Localization Of Ack49/51 14-3-3 Proteins and Hbmentioning
confidence: 99%
“…The survival of MSCs is a significant point to be made about the use of epidrugs in promotion of MSC differentiation. The results of studies have shown that the viability of MSCs was affected by various doses of epidrugs; increased doses had a negative impact on MSC survival [ 117 , 119 , 132 ]. An evaluation of the effect of VPA and NaBu on MSCs showed a dose-dependent reduction in MSC proliferation.…”
Section: Epigenetic Modifiers Known As Epidrugsmentioning
confidence: 99%